Morphological brain measures of cortico‐limbic inhibition related to resilience. Issue 9 (28th December 2016) - Gupta, Arpana; Love, Aubrey; Kilpatrick, Lisa A.; Labus, Jennifer S.; Bhatt, Ravi; Chang, Lin; Tillisch, Kirsten; Naliboff, Bruce; Mayer, Emeran A.
Abstract : Resilience is the ability to adequately adapt and respond to homeostatic perturbations. Although resilience has been associated with positive health outcomes, the neuro‐biological basis of resilience is poorly understood. The aim of the study was to identify associations between regional brain morphology and trait resilience with a focus on resilience‐related morphological differences in brain regions involved in cortico‐limbic inhibition. The relationship between resilience and measures of affect were also investigated. Forty‐eight healthy subjects completed structural MRI scans. Self‐reported resilience was measured using the Connor and Davidson Resilience Scale. Segmentation and regional parcellation of images was performed to yield a total of 165 regions. Gray matter volume (GMV), cortical thickness, surface area, and mean curvature were calculated for each region. Regression models were used to identify associations between morphology of regions belonging to executive control and emotional arousal brain networks and trait resilience (total and subscales) while controlling for age, sex, and total GMV. Correlations were also conducted between resilience scores and affect scores. Significant associations were found between GM changes in hypothesized brain regions (subparietal sulcus, intraparietal sulcus, amygdala, anterior mid cingulate cortex, and subgenual cingulate cortex) and resilience scores. There were significant positive correlations between resilience and positive affect and negative correlations with negative affect. Resilience was associated with brain morphology of regions involved in cognitive and affective processes related to cortico‐limbic inhibition. Brain signatures associated with resilience may be a biomarker of vulnerability to disease. © 2016 Wiley Periodicals, Inc. Abstract : The relationship between resilience measures and morphology of regions involved in cognitive and affective processes are demonstrated, consistent with previous suggestions that individuals with low resilience may have compromised cortico‐limbic inhibition, increasing their vulnerability to stress related morbidity. Higher resilient individuals have a better ability to bounce back from adverse events, have greater emotional and cognitive control, and are more persistent.